Adsorptive removal of acrylic acid from the aqueous environment using raw and chemically modified alumina: Batch adsorption, kinetic, equilibrium and thermodynamic studies. Issue 4 (August 2020) - Khan, Hamayun; Iram,; Gul, Kashif; Ara, Behisht; Khan, Adnan; Ali, Nauman; Ali, Nisar; Bilal, Muhammad
Abstract: Herein, raw alumina was chemically modified using strong acid (HCl) and base (NaOH) to constitute alumina adsorbents, which were applied for the removal of an emerging pollutant, acrylic acid from the aqueous environment. The as-synthesized alumina samples were characterized using FT-IR, SEM, EDX, and surface area analyzer. Characterization results revealed that the chemical modification of alumina did not affect its chemical nature. SEM images demonstrated the porous nature of alumina with irregular shape and rough texture. EDX data shows the elemental composition as Al and O in raw alumina while Cl and Na were found as additional elements in acid (HCl) alumina and base (NaOH) modified alumina, respectively. BET specific surface area of alumina samples was in the range from 155.63–158.36 m 2 /g. The point of zero charges (PZC) was also determined and found to be 5.9, 6.4 and 9.0 for raw, acid (HCl) and base (NaOH) modified alumina, respectively. In the adsorption study, pH 4.5, 25 °C and 72 and 24 h using the raw and chemically modified alumina, respectively, were found to be the best experimental conditions using 0.1 mol/L acrylic acid solution and 1.0 g alumina. During the consecutive desorption experiments, 86.9 ± 2.5–95.5 ± 3.8 % acrylic acid was desorbed at pH 13. The data follows the pseudo-second-order kinetic and Freundlich adsorption models with 4080–4330 μmol/g adsorption capacity. Moreover, the adsorption process was non-spontaneous and exothermic with the lowering of the randomness of the system at the solid-solution boundary. In conclusion, the high uptake capacity and recyclable nature of the alumina adsorbents render them as promising candidates for the remediation of wastewater and industrial effluents containing such toxic pollutants.